2020
DOI: 10.1177/1460458220954610
|View full text |Cite
|
Sign up to set email alerts
|

Social media in ophthalmology: An analysis of use in the professional sphere

Abstract: To characterize how ophthalmologists are using social media in their practice. A survey regarding ophthalmologists’ personal and professional use of social media was distributed online through a university alumni listserv. Data collection occurred over 4 weeks from January to February 2020. In total, 808 ophthalmologists opened the survey email, and 160 responded (19.8%). Of 160 respondents, 115 (71.9%) participated in social media for personal use. Professional use of social media was noted by 63 (39.4%) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…11 In contrast, there was no significant difference in the rates of professional social media use between trainees and attending ophthalmologists. 10 Many professional accounts are often run by social media managers or by the institutions employing ophthalmologists, which may influence this finding. 10 Additionally, the perceived Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast, there was no significant difference in the rates of professional social media use between trainees and attending ophthalmologists. 10 Many professional accounts are often run by social media managers or by the institutions employing ophthalmologists, which may influence this finding. 10 Additionally, the perceived Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients were identified as the target population of social media pages among 34.9% of the ophthalmologists surveyed, while both patients and other professionals were the target for an additional 55.6% of respondents. 4 Clarke et al analyzed Lasik surgery Instagram and Twitter posts by patients using the hashtag #lasiksurgery. The investigators found that 92% of patients posted photographs, 88% had a positive tone, 62% referenced the clinic at which they were treated, and 44% posted during the day of the procedure.…”
Section: Patient Outreachmentioning
confidence: 99%
“…For example, platforms were used to send instructions and appointment reminders to post-operative cataract patients. 4 In one study, investigators found that messaging patients regarding post-operative instructions after cataract surgery led to better medication compliance at one week, 6 though this effect was lost at the one-month mark. Overall, social media may be leveraged in the future alongside email and medical record messaging applications to more effectively reach patients.…”
Section: Patient Outreachmentioning
confidence: 99%
See 2 more Smart Citations